2018
DOI: 10.1002/csr.1704
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, social, and governance and company profitability: Are financial intermediaries different?

Abstract: This paper investigates the association between environmental, social, and governance (ESG) disclosure and company profitability, as measured by return on assets (ROA). We first assess a method to indexing the ESG score of a large sample of U.S. listed companies based on MSCI ESG KLD STATS data from 2000 to 2016. The statistical model is run on 17,358 observations and studies the association of ROA and the three different dimensions of ESG score. Significant differences between industrial firms and financial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
119
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(184 citation statements)
references
References 68 publications
11
119
1
Order By: Relevance
“…In the first-stage quantitative research, we were facing a lack of access to the necessary data to conduct our study in a full scale. We are able only to collect data related to the ROE (one of short-term indicators of financial performance) of Brogi and Lagasio (2019) Association between environmental, social, and governance disclosure and company profitability measured by ROA…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first-stage quantitative research, we were facing a lack of access to the necessary data to conduct our study in a full scale. We are able only to collect data related to the ROE (one of short-term indicators of financial performance) of Brogi and Lagasio (2019) Association between environmental, social, and governance disclosure and company profitability measured by ROA…”
Section: Methodsmentioning
confidence: 99%
“…The comprehensive analysis carried out by Waheed and Yang (2019) on 450 small and medium enterprises (SMEs) from Pakistan unveiled the significantly higher effect of external CSR disclosure than internal CSR disclosure on marketing and sales performance. Brogi and Lagasio (2019) Although many extant studies focus on the relation between CFP and CSR reporting, less attention has been given to the shifting role of financial performance in CSR reporting in a changing institutional environment. Sun, Zhao, and Cho (2019) have investigate whether, why, and how institutional transitions affect the role of financial performance in CSR reporting in terms of firms' propensity to issue standalone CSR reports, the quality of voluntary CSR reports, and the quality of mandatory CSR reports.…”
Section: Corporate Sustainable Development and Cfpmentioning
confidence: 99%
“…From a theoretical point of view, researcher may further investigate differences resulting by a cross-country and cross-industry sample construction (Brammer & Pavelin, 2008;Brogi & Lagasio, 2018). Indeed, as concerns the former, the sample of analysis is not reliable for a subgroup analysis that investigates different and similarities between countries.…”
Section: Family Ownershipmentioning
confidence: 99%
“…Qiu et al (2019) also found that environment, society, and governance have different impacts on these financing costs; only the dimensions of environment and governance can ultimately reduce them [33]. When they studied the relationship between ESG's three-dimension disclosure scores and ROA, Brogi et al (2019) found that all three dimensions were positively correlated with ROA, but S was the most correlated with ROA [34]. Based on this, this study discusses the relationship between firm value and the three dimensions of environment, society, and governance and discusses whether the information disclosure of each dimension has a consistent or positive impact on firm value.…”
Section: Esg Information Disclosure and Firm Valuementioning
confidence: 99%
“…This view has been confirmed by some scholars. If an enterprise invests too much money in social responsibility activities, its consumers will think that the enterprise overuses scientific research funds, that the product quality is not guaranteed, or that the enterprise's performance will be reduced [7,35]. Similarly, Coluccia et al (2019) found that there is a substitution effect occurring between investment in R&D and ESG scores.…”
Section: Interaction Effect Of Green Innovation and Esg On Firm Valuementioning
confidence: 99%